CHARACTERIZATION OF COLOMBIAN QUESILLO CHEESE BY SPECTROCOLORIMETRY - RAMÍREZ NAVAS Ph.D., Juan Sebastián; RODRÍGUEZ DE STOUVENEL Ph.D., Aida (Vitae, 2012)
Rationale: The colour of food is one of the major attributes which affect a consumer’s perception of its quality, and it is also a powerful tool for quality control and marketing. The Quesillo cheese is a typical Colombian cheese. The observed colour in Quesillo cheese is a composite of many contributing factors. Objectives: The objective of the current work was to characterize the colour of Quesillo cheese using parameters L*, a* and b* of the CIE (Commission Internationale d’Eclairage) system by spectrocolorimetry. Methods: The collection of data with colorimeters was used for the instrumental characterization of colour in Quesillo cheese. Colour parameters L*, a* and b* were measured in triplicate using CIE-LAB space for fourteen commercial Quesillo cheese and seven manufactured cheeses. Using the mean values of colour in the analysed cheeses, parameters of chroma metric (C*), hue (H*), colour differences (ΔE), whiteness index (WI) and yellowness indix (YI) were determined. Results: The general mean values obtained were, L*= 78.13, a*= -0.96, b* = 22.95, C*= 22.97 and H*= 92.38°. These can be estimated as the reference values for Quesillo cheese, which could be used in quality control in the manufacturing process. Different factors are discussed that can change or influence the colour in the final product. Conclusions: <ZThe colour variations of this type of cheese are principally due to the initial composition of milk, composition of acid whey and manufacturing technology.